Anestezjologia i intensywna terapiaHow can we increase chances of the patient in cardiogenic shock? - Nadziakiewicz, Paweł; Knapik, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Cardiogenic shock complicating acute myocardial infarction is noticed in about 7% of the patients. Despite advances in its management mortality is still very high and reaches 50%. A strategy for early revascularization infarct-related artery is essential in the management of patients with shock. Besides that various techniques of circulatory support is needed including use of inotropic drugs, intra-aortic baloon pump counterpulsation or ventricular assist devices. Advanced techniques of critical care medicine are important for effective management. Patients are ventilated mechanically to improve and maximize oxygenation. Renal function is supported by hemofiltration. All these therapies are intended to reverse profound disturbances of homeostasis caused by diminished cardiac output and systemic inflammatory response.